Analysis of Depth and Liquid Density Factor at Hydrostatic Pressure Assisted by PhET Simulation - Syuzita, Amalia (International Journal of Science Education and Science, 2024)
The study has been conducted to analyze the depth factor of liquids and the density factor of liquids assisted by PhET simulation. This research is quantitative descriptive research with data presented descriptively, tables, and graphs. The data is obtained through a simulation of hydrostatic pressure in a PhET simulation. The results show that the relationship between the density of the liquid and the depth of the liquid to the pressure of the liquid is directly proportional. If the density of the liquid and the depth of the liquid are greater, the pressure will also be greater. The application of hydrostatic pressure is seen in the design of submarines which need to take into account the amount of hydrostatic pressure in the sea.